Analysis of the Impact of Changes in the Indonesian Mortality Table III to IV on Life Insurance Premiums Using the Gompertz–Makeham Model Approach - Sitorus, Nadicta Eunike; Saldi, Aqil Afrizqal; Sagala, Regilpa (Universitas Islam Negeri Raden Intan Lampung, 2026)
Life insurance premium determination is highly sensitive to mortality assumptions, which are typically represented through actuarial mortality tables. The transition from the Indonesian Mortality Table III (2011) to Table IV (2019) reflects structural shifts in population mortality that may alter both actuarial valuation and model behavior. Despite its importance, limited research has examined how such changes influence premium outcomes within a continuous mortality modeling framework. This study aims to investigate the impact of mortality table transitions on life insurance premiums using the Gompertz–Makeham model, with particular emphasis on parameter sensitivity and model consistency. Secondary data of age-specific mortality probabilities for individuals aged 20–60 years, classified by gender, were transformed into continuous mortality rates and estimated using numerical optimization techniques. Model performance was assessed through the alignment between observed and fitted mortality patterns, as well as the exponential growth structure implied by the model. Premium calculations were conducted using the net single premium approach under a constant interest rate assumption. The results show that the updated mortality table systematically reduces premium values by a measurable margin, with stronger effects observed at older ages. Furthermore, the findings reveal that parameter changes significantly influence the stability and responsiveness of the mortality model. This study contributes by offering a quantitative sensitivity-based framework that integrates mortality table transitions into continuous actuarial modeling, thereby enhancing the accuracy and reliability of premium estimation.